P101 Remote risk stratification of dyspnoea in acute respiratory disorders and applications for COVID-19 and future pandemics: a systematic review of the literature. (8th April 2021) - Dominic, Catherine; Khare, Yuti; Ponnapalli, Anuradha; Ganesh, Shivani; Bhalla, Gaurav; Gokani, Shyam; Ponnapalli, Anuradha
Abstract: Background: Due to the highly infectious nature of the disease, a large amount of community-based triage of COVID-19 is performed by video/telephone consultation, especially in primary care. This presented clinicians with a new challenge in risk stratification of patients with dyspnoea due to suspected COVID19. This review searched existing literature to identify existing modalities to remotely assess patients with acute respiratory distress, which can be adapted for the COVID-19 pandemic and in future similar situations. Methods: We conducted a systematic search of Medline, Embase and Medrxiv for studies of the remote assessment of dyspnoea in acute respiratory disorders in adults/children. The study was registered on PROSPERO (ID: CRD42020202292): 3014 abstracts were screened independently by two reviewers and 32 studies were progressed to full text screening. Results: Five studies were selected for review, including 1317 patients. Two studies assessed video consultation, two assessed telephone related triage tools, and one study assessed an online triage tool for dyspnoea. In one study, video consultation was found to have 83% sensitivity for diagnosing 'severe' respiratory distress in comparison to face-to-face assessment. The online triage tool was found to have 87.5% sensitivity for detecting dyspnoea requiring emergency level care. Conclusion: A range of successful remote risk stratification tools and clinical features were identified for assessing dyspnoea severity which can be adapted to COVID-19 and future pandemics to assess respiratory distress via telemedicine. These findings will influence development of comprehensive evidence-based tools to assess dyspnoea which will reduce resource strain during current/future pandemics. References: Loinaz C, Marcacuzco A, Fernández-Ruiz M, Caso O, Cambra F, San Juan R, et al. Varied clinical presentation and outcome of SARS-CoV-2 infection in liver transplant recipients: Initial experience at a single center in Madrid, Spain. Transpl Infect Dis Off J Transplant Soc. 2020 Jun 20;e13372.